Characteristic Respondents With Creatinine Levels In Patients Undergoing Hemodialysis - Daryaswanti, Putu Intan; Putri, Ni Komang Dima Listyana; Yudhawati, N.L.P Suardhini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Background: Kidneys have an important role in the body to maintain electrolyte composition, volume stability, and extracellular fluid. The important function of the kidneys is to filter the end products or waste products of the body's metabolism, for example creatinine. Creatinine level is a parameter of renal function, so it is necessary to know the patient characteristics related to creatinine levels. The purpose of this study was to analyze the relationship between the characteristics of age, sex, occupation and duration of hemodialysis with the creatinine levels of patients undergoing hemodialysis. Method: This study used an analytic cross-sectional study design. The population of this study were 74 patients with chronic renal failure who underwent regular hemodialysis twice a week in Bangli Hospital. The sampling technique used was purposive sampling. Creatinine data is secondary data obtained from documents written in the Hemodialysis Room at Bangli Hospital. Results: the occupation with creatinine levels (p = 0.099), sex with creatinine levels (p = 0.094), length of hemodialysis with creatinine levels (p = 0.406), age with creatinine levels (p = 0.046). Conclusion: there is a relationship between age characteristics and creatinine levels in patients undergoing hemodialysis.  Abstrak: Latar Belakang: Ginjal memiliki peran penting dalam tubuh untuk menjaga komposisi elektrolit, kestabilan volume, dan cairan ekstraseluler. Fungsi penting ginjal adalah menyaring produk akhir atau produk sisa metabolisme tubuh, misalnya kreatinin. Kadar kreatinin merupakan salah satu parameter fungsi ginjal, sehingga perlu diketahui karakteristik penderita yang berkaitan dengan kadar kreatinin. Tujuan penelitian ini adalah untuk menganalisis hubungan karakteristik umur, jenis kelamin, pekerjaan dan lama hemodialisis dengan kadar kreatinin pasien yang menjalani hemodialisis. Metode: Penelitian ini menggunakan desain penelitian cross-sectional analitik. Populasi penelitian ini adalah 74 pasien gagal ginjal kronik yang menjalani hemodialisis rutin dua kali seminggu di RSUD Bangli. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Data kreatinin merupakan data sekunder yang diperoleh dari dokumen yang tertulis di Ruang Hemodialisis RSUD Bangli. Hasil: pekerjaan dengan kadar kreatinin (p = 0,099), jenis kelamin dengan kadar kreatinin (p = 0,094), lama hemodialisis dengan kadar kreatinin (p = 0,406), usia dengan kadar kreatinin (p = 0,046). Kesimpulan: Ada hubungan karakteristik usia dengan kadar kreatinin pada pasien yang menjalani hemodialisis.